Analysis of risk factors for vitreous hemorrhage and recurrent hemorrhage after vitrectomy in patients with diabetic retinopathy - Shuwen Lu; Haoyu Li; Chao Ma; Xian Li (BMC Ophthalmology)
Abstract Purpose To investigate the risk factors associated with recurrent hemorrhage following vitrectomy surgical intervention for diabetic retinopathy (DR). Methods A retrospective analysis was conducted on 579 eyes diagnosed with DR necessitating surgical intervention. These cases were categorized into two groups: recurrent hemorrhage and non-recurrent hemorrhage. Comparative, random forest (RF), and regression analyses were subsequently performed to evaluate variables pertaining to patients’ demographic information, clinical examination and blood test results, treatment approaches, lifestyle habits, and overall health status. Results This study compared patients with recurrent and non-recurrent hemorrhages, revealing significant differences in factors such as endodiathermy, anticoagulant use, cerebrovascular diseases, smoking status, glycosylated hemoglobin levels and BMI. Patients with no recurrent hemorrhage have faster vision recovery. The univariable logistic regression analysis indicated that cerebrovascular disease (OR = 7.87, P < 0.001), anticoagulant use (OR = 16.72, P < 0.001), and elevated glycated hemoglobin levels (OR = 21.22, P < 0.001) exhibited strong associations with recurrent hemorrhage. The multivariable logistic regression analysis indicated that recurrent hemorrhage risk factors include anticoagulant use (OR = 120.77, P = 0.020) and glycated hemoglobin levels (OR = 18.41, P = 0.001). Conclusions Recurrent postoperative hemorrhage is influenced by several factors, notably the use of intraoperative endodiathermy, adjustments in ocular therapy, and management of the patient’s systemic condition. In clinical practice, careful consideration of these factors is essential to mitigate postoperative hemorrhage in patients.